Intensive Care Units in Malaysia: Scope for improvement - Mat Nor, Mohd Basri (International Islamic University Malaysia, 2019)
The demand of critical care service in Malaysia is expected to increase as population age, comorbidities increase and expectation rises, reflecting global trends. Asia accounts for at least half of the cases of sepsis, ARDS and mechanical ventilation in the world. The concept of ICU is accepted today as an integral part of almost every general hospital in Malaysia. T